2016
DOI: 10.5433/1679-0359.2016v37n2p997
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of elephant grass silages supplemented with different levels of dehydrated cashew bagasse

Abstract: The objective of the present study was to evaluate the chemical composition of elephant grass silages supplemented with different levels dried cashew bagasse (DCB). Our experiment used a randomized design replicated four times, each replicate consisting of the following five treatments: 100% elephant grass; 95% elephant grass + 5% DCB; 90% elephant grass + 10% DCB; 85% elephant grass + 15% DCB; and 80% elephant grass + 20% DCB. The elephant grass was cut manually to a residual height of 5 cm at 80 days of age,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 7 publications
3
4
3
2
Order By: Relevance
“…These results demonstrated that the addition of mango residue in elephant grass and cassava peel silages provides an adequate fermentation due to the addition of NFC, providing the supply of soluble sugars for acid lactic bacteria. The findings of this study corroborated Guerra et al (2016) that working with elephant grass silage with dehydrated cashew bagasse obtained similar results, indicating an improvement in the fermentation of the silage.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…These results demonstrated that the addition of mango residue in elephant grass and cassava peel silages provides an adequate fermentation due to the addition of NFC, providing the supply of soluble sugars for acid lactic bacteria. The findings of this study corroborated Guerra et al (2016) that working with elephant grass silage with dehydrated cashew bagasse obtained similar results, indicating an improvement in the fermentation of the silage.…”
Section: Resultssupporting
confidence: 89%
“…Quadratic behavior was observed for the OM, CP, EE, NDF and ADF with maximum points of 91.1%, 9.64%, 1.88%, 41.6% and 25.2% with inclusion of 14.6%, 10.7%, 8.62%, 9.11%, and 9.54% (Table 3). The maximum (P<0.05) CP content obtained in this study was higher than that recorded by Azevedo et al (2017) of 6.60% with the inclusion of 16.1% mango residue in elephant grass silage; by Rêgo et al (2010) of 6.21%, with 16.0% by-product of the mango processing and by Ferreira et al (2015) and Guerra et al (2016) 9.10% and 6.45% with the addition of 14% and 20% dehydrated cashew residue, respectively. The reduction in CP levels in elephant grass and cassava peel silages with the addition of mango residue above 11% could be related to the lower protein content of the additive.…”
Section: Resultscontrasting
confidence: 71%
See 1 more Smart Citation
“…Thus, the use of fruit processing by-products as additives during elephant grass ensiling has increased (Ferreira et al, 2015;Guerra et al, 2016). These by-products are usually dehydrated and their usage increases the dry matter of elephant grass silage and provides greater amounts of non-fibre carbohydrates, which contribute to a more rapid drop in pH and, consequently, a better stability and quality of the silage (Rêgo et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies (Lukkananukool et al, 2013, Epifanio, Costa, Severiano, Bento, & Perim, 2014, Figueredo et al, 2014, Menezes et al, 2016, Guerra et al, 2016 fermentative process and the reduction of losses of tropical grass silages, among which the use of additives was highlighted. In this sense, the adsorbent additives, characterized by reducing or eliminating effluent production, may assume relevance in the production of forage grass silages with high moisture content.…”
Section: Introductionmentioning
confidence: 99%